Minding your own small business an introductory curriculum for small business management - Holt, Nancy; Shuchat, Jo; Regal, Mary Lewis (Washington : U.S. government printing office, 1979)
This volume of the entrepreneurship instructional materials, minding your own small business, something ventured, something gained, location decisions and mini- problems in entrepreneurship were created by project staff with the help of many people.
ahz 04/04/2019
Loans
Keywords: Enterpreneur; Business management